The Topos of Childhood in Modern Poetry (1939–1989) - Mielhorski, Robert (Tematy i Konteksty, 2021)
The paper problematises the literary image of childhood in poetry in relation to external historical and socio-political events. The material analysed covers Polish poetry from 1939 – 1989 (a clearly distinguished segment of the historical-literary process). The choice and ordering of the case studies results from the application of two research paradigms: (i) the paradigm concerned with autobiographical motifs, which refers to such topics of 20th century writings as exile (poetry of return by Łobodowski, Wierzyński etc.) immigration (nostalgic [pansentimentalism] and emotionally neutral motifs), Holocaust (motifs of fear, division between now and then, the role of imagination) and (ii) a generation-related paradigm, which allows us to follow the topos of childhood viewed from the perspective of history according to the order of generations entering Polish literature (from the 1920 Generation to the New Wave Groups) up to the succession of consecutive literary trends in the second half of the 20th century (e.g. soc-realism and soc-plans). Poetic texts concerning childhood in the light of history are viewed as records of “rites of passage” operating from the child’s phase of the pre-personalisation area - the child’s sense of being one with the world, experiencing the harmony of being - to the period of personalisation - when history leaves its mark on this period; characterised by the sense of one’s distinctiveness from reality, individual alienation, the need for rationalisation of one’s own existence and the existence of the surrounding reality. The role of history is to lead the child from the pre-personalistic period to the experience of personalisation.